Identification of Linear B-Cell Epitopes on Hemagglutinin Protein of Canine Distemper Virus Using Two Monoclonal Antibodies - Shi, Pengfei (Front Vet Sci, 2020)
Canine distemper virus (CDV) belongs to the Morbillivirus genus of the Paramyxoviridae family, which causes a threat to the domestic dog and fur-animal industry. Hemagglutinin protein is a major membrane protein of the vital molecular factor in CDV tropism, also known to induce hosts to produce neutralizing antibodies. In the current study, we prepared two monoclonal antibodies, 1A5 and 2B8, against the H protein of the CDV-PS strain. A series of partially overlapping synthetic peptides covering the hemagglutinin protein (amino acids 50–204) were screened to define the linear epitope identified by 1A5 and 2B8 mAbs. (120)QKTNFFNPNREFDFR(134) (F8) and (178)ARGDIFPPY(186) (F14-1) are minimal linear epitopes recognized by 1A5 and 2B8 mAbs, respectively. Further investigations revealed that F8 is conserved in different CDV strains; however, F14-1 contains mutant residues 178, 179, and 180. The epitopes F8 and F14-1 localized at the surface of hemagglutinin protein in a three-dimensional (3D) structure. CDV-infected dog serum can also recognize the identified B-cell epitopes.